2011
DOI: 10.1007/s12289-011-1028-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological and crystal plasticity approaches to describe the mechanical behaviour of Ti6Al4V titanium alloy

Abstract: This paper presents a multiscale study of the quasi-static behaviour of a Ti6Al4V titanium alloy sheet. Tensile and compressive tests were carried out on specimens along several orientations from the rolling direction in order to characterise the material anisotropy. In parallel, X-Ray diffraction texture measurements were performed before and after deformation in tension. A phenomenological model (CPB06exn) and a multiscale crystal plasticity model (Multisite) were investigated to describe the mechanical beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The FC Taylor model was used to generate the virtual data and the authors concluded that a more advanced CP model is required to arrive at a sufficiently accurate calibration procedure. Hammami et al [27] showed that the Multisite model provides an accurate anisotropy prediction for Ti6Al4V under tensile stress states. The authors concluded that the Multisite model can be used to limit the experimental effort associated with the calibration of advanced anisotropic yield functions such as CPB06.…”
Section: Introductionmentioning
confidence: 99%
“…The FC Taylor model was used to generate the virtual data and the authors concluded that a more advanced CP model is required to arrive at a sufficiently accurate calibration procedure. Hammami et al [27] showed that the Multisite model provides an accurate anisotropy prediction for Ti6Al4V under tensile stress states. The authors concluded that the Multisite model can be used to limit the experimental effort associated with the calibration of advanced anisotropic yield functions such as CPB06.…”
Section: Introductionmentioning
confidence: 99%
“…A phenomenological model and a multiscale crystal plasticity model were put forward in theory by Hammami et al. [7] to describe the mechanical behavior anisotropy of the tensile and compressive tested material. Other researchers combined theoretical methods and experimental methods in studying the anisotropy of the materials processing and properties like Jurendic et al [8] who developed a numerical simulation method to aid forming tool steel.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31] Similarly, the in-house thermo-mechanical constitutive relationships for performance metric modeling are addressed in the literature. [17,20,21,[32][33][34][35][36] The computational complexity for currently available finite element algorithms to simulate a full-sized part which fills an SLM machine has been demonstrated to be intractable, [37] even for the most powerful supercomputers. The present simulation environment includes an attempt to solve the problem with intelligent solver algorithms and inclusion of problem specific asymptotics (Figures 7 and 8).…”
Section: A Preprocessing Stagementioning
confidence: 99%